In Vivo Articular Cartilage Regeneration Using Human Dental Pulp Stem Cells Cultured in an Alginate Scaffold: A Preliminary Study - Manuel Mata; Lara Milian; Maria Oliver; Javier Zurriaga; Maria Sancho-Tello; Jose Javier Martin de Llano; Carmen Carda (Hindawi Limited, 2017)
Osteoarthritis is an inflammatory disease in which all joint-related elements, articular cartilage in particular, are affected. The poor regeneration capacity of this tissue together with the lack of pharmacological treatment has led to the development of regenerative medicine methodologies including microfracture and autologous chondrocyte implantation (ACI). The effectiveness of ACI has been shown in vitro and in vivo, but the use of other cell types, including bone marrow and adipose-derived mesenchymal stem cells, is necessary because of the poor proliferation rate of isolated articular chondrocytes. In this investigation, we assessed the chondrogenic ability of human dental pulp stem cells (hDPSCs) to regenerate cartilage in vitro and in vivo. hDPSCs and primary isolated rabbit chondrocytes were cultured in chondrogenic culture medium and found to express collagen II and aggrecan. Both cell types were cultured in 3% alginate hydrogels and implanted in a rabbit model of cartilage damage. Three months after surgery, significant cartilage regeneration was observed, particularly in the animals implanted with hDPSCs. Although the results presented here are preliminary, they suggest that hDPSCs may be useful for regeneration of articular cartilage.